Perspectives of a new liberalisation round - Wilhelm Hanemann (Intereconomics, 1972)
The dollar crisis and the temporary import surcharge imposed by the Nixon Administration have awakened the free-enterprise world to the dangers of creeping protectionism. But what must now be done in order to secure trade liberalisation? The following articles deal with this very important question.
Keywords: 330; Foreign Trade